2002
DOI: 10.1039/b205053f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, molecular structure and emission properties of benzoato-bridged lanthanide complexes with hydrotris(pyrazolyl)borate

Abstract: Reaction of GdCl3 and TbCl3 with one equivalent of the potassium salt of the tridentate ligand hydrotris(pyrazol-1- yl)borate [K(tp)] and two equivalents of sodium p-X-benzoate (X = H, Cl, Br and NO2) yielded the complexes 1-6 of composition [(tp)Ln(mu-p-X-OBz)(2)}(2)] (Ln = Gd, Tb) whereas the reaction of TbCl3 with 2 equivalents of [K(tp)] and one equivalent of sodium azide, gave the tetranuclear complex [{tp)(2)Tb(mu-N- 3)}(4)] (7). The crystal structures of the benzoate complexes (X = H) of Gd (1) and Tb (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Bulky ligands on lanthanoid atoms have been frequently employed to lend lanthanoid azides more stability towards mechanical shock or temperature changes, and also to increase the solubility in organic and unipolar solvents. Targets of these works are the preparation of phosphors or of molecular nitrides of the lanthanoids, which still seem to be elusive …”
Section: Introductionmentioning
confidence: 99%
“…Bulky ligands on lanthanoid atoms have been frequently employed to lend lanthanoid azides more stability towards mechanical shock or temperature changes, and also to increase the solubility in organic and unipolar solvents. Targets of these works are the preparation of phosphors or of molecular nitrides of the lanthanoids, which still seem to be elusive …”
Section: Introductionmentioning
confidence: 99%
“…For properties of rare earth compounds derived from carboxylic acids, see: Chin et al (1994); Singh et al (2002). For related compounds, see: Jin et al (1996); Gubina et al (2000); Wang et al (2003); Qiu et al (2007); Ooi et al (2010).…”
Section: Related Literaturementioning
confidence: 99%
“…Data collection: CrysAlis PRO (Oxford Diffraction, 2010); cell refinement: CrysAlis PRO; data reduction: CrysAlis PRO; program(s) used to solve structure: SHELXS97 (Sheldrick, 2008); program(s) used to refine structure: SHELXL97 (Sheldrick, 2008); molecular graphics: DIAMOND (Brandenburg, 1999); software used to prepare material for publication: SHELXL97. Because of their excellent luminescent properties (Chin et al, 1994;Singh et al, 2002), rare earth-carboxylic acid complexes have been widely studied and applied in many fields. Distinct structure features with various rare earths (Qiu et al, 2007;Gubina et al, 2000) or ligands (Jin et al, 1996;Wang et al, 2003) have been reported.…”
Section: Tablementioning
confidence: 99%
“…5b Over the last 15 years, dinuclear Ln-Ln complexes with bridging carboxylate type ligands have been studied from different view points. [6][7][8][9][10] The latest study on the benzoate bridged Ln() complexes focused on the synthesis, X-ray structures and emission properties, but the targeted lanthanide ions were limited to only three Gd and Tb complexes. 10 Though the metal-metal interactions and chiroptical properties for the tetracarboxylate bridged dinuclear transition metal complexes of the type, M 2 (O 2 CR) 4 L 2 have been studied (showing only vicinal chirality due to optically active RCO 2 ) for a few decades, 11 there are no systematic chiroptical studies on this type of Ln 2 (O 2 CR) 4 L 2 complexes with configurational chirality.…”
Section: Introductionmentioning
confidence: 99%